The voicelessness of theology and religious studies in contemporary Africa : who is to blame and what has to be done? Setting a new agenda - Amanze, James N. (Missionalia : Southern African Journal of Mission Studies, 2012)
This paper examines the voicelessness of theology and religious studies in post-independence Africa. It investigates the possible factors that have led to this phenomenon and explores ways and means whereby theology and religious studies can once again regain their rightful position not only in the academia, but also in society as a whole. It argues that unless theologians and religious educators make a radical U-turn to transform theology and religious studies into something meaningful and attractive, these two subjects will continue to be relegated to a second-class category of academic disciplines with disastrous consequences for theological and religious educators, as well as theological institutions.
Free